2015
DOI: 10.1088/1468-6996/16/4/045003
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-responsive cell culture carriers based on poly(vinyl methyl ether)—the effect of biomolecular ligands to balance cell adhesion and stimulated detachment

Abstract: Two established material systems for thermally stimulated detachment of adherent cells were combined in a cross-linked polymer blend to merge favorable properties. Through this approach poly(N-isopropylacrylamide) (PNiPAAm) with its superior switching characteristic was paired with a poly(vinyl methyl ether)-based composition that allows adjusting physico-chemical and biomolecular properties in a wide range. Beyond pure PNiPAAm, the proposed thermo-responsive coating provides thickness, stiffness and swelling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 54 publications
0
20
0
1
Order By: Relevance
“…Structure formulae of applied blend components are shown in Figure 1 . Additional information on physico-chemical characterization of TRP coatings by spectroscopic ellipsometry, nanoindentation, and X-ray photoelectron spectroscopy is given in Teichmann et al 18 , 19 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Structure formulae of applied blend components are shown in Figure 1 . Additional information on physico-chemical characterization of TRP coatings by spectroscopic ellipsometry, nanoindentation, and X-ray photoelectron spectroscopy is given in Teichmann et al 18 , 19 …”
Section: Methodsmentioning
confidence: 99%
“…A high/low irradiation dose during electron beam cross-linking leads to low/high degree of swelling below the transition temperature, which corresponds to a high/low elastic modulus of the swollen material. 18 , 19 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies to date have investigated the potential of the thermo-responsive polymer, PNIPAM, for corneal cell type detachment. 8,[35][36][37] We have recently shown that blend electrospinning of thermo-responsive polymer poly (PEGMA 188 ) with a bulk polymer of choice (amenable to electrospinning) will render the fibres thermo-responsive. Mammalian cell adhesion, viability, proliferation and phenotype on this fibrous culture system over numerous thermal enzyme-free passages was achieved.…”
Section: Enzymatic-free Passagingmentioning
confidence: 99%